Integrating Sustainability in Resource-Constrained Environments: A Qualitative Study of Indonesian MSMEs. - Novani Elika Saputri (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2025)
Sustainability has become an important issue in business development, including within Micro, Small, and Medium Enterprises (MSMEs) operating in resource-constrained environments. Despite their significant contribution to economic growth and employment, many MSMEs face limitations in financial resources, technology, and access to sustainability-related knowledge. This study aims to explore how MSMEs integrate sustainability practices within resource-constrained environments, focusing on MSMEs in Palembang, Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and documentation involving several MSME actors from different business sectors. Data were analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing and verification. The findings reveal that sustainability integration among MSMEs often emerges through adaptive and practical strategies rather than formal sustainability frameworks. MSME actors tend to implement sustainability through efficient use of local resources, waste reduction, reuse of materials, and energy-saving practices in daily business operations. These practices are primarily driven by economic efficiency and business survival rather than regulatory pressure or environmental awareness alone. The study highlights that sustainability in resource-constrained MSMEs develops through contextual and experience-based strategies that align economic needs with environmentally responsible practices. The findings contribute to the literature on sustainable entrepreneurship by providing empirical insights into grassroots sustainability practices among small enterprises in developing economies. Practically, the study suggests that policymakers should design more context-sensitive sustainability programs that support MSMEs through capacity building, access to knowledge, and resource-efficient business practices.